Learning to lead: an investigation into the preparation, induction, roles and practices of beginning principals: a Canadian study - Northfield, Shawn K. (2011)
The growing complexity regarding a principal's role and associated leadership tasks, combined with changing societal realms and educational reform pose serious challenges to even the most experienced educational leaders. For new school leaders, taking on the principalship within a given organizational context is predicated on the notion that learning the role is a continual process of "being and becoming."